Spectral Theory in Fuzzy Normed Spaces - A, Abdul-Samee; K, Ahlam Jameel; C, Faria Ali (Al-Nahrain Journal of Science, 2011)
In this paper we give some definitions related to spectral theory of a linear operator T defined on a fuzzy normed space and we prove that spectrum σ(T) and resolvent set ρ(T) are nonempty for a fuzzy bounded linear operator defined on certain fuzzy normed spaces. Moreover, we show ρ(T) is τ-open and σ(T) is τ-closed.